PENEGAKAN HUKUM BAGI PERUSAHAAN YANG MELAKUKAN TRANSAKSI ELEKTRONIK MELALUI E-COMMERCE SEBAGAI PERLINDUNGAN HUKUM TERHADAP PENGGUNA - Halim, Santoso; Franciska, Wira; Noor, Zulki Zulkifli (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The internet has brought the world economy into a new phase which is more popularly known as digital economics. Its existence is marked by the increasingly widespread economic activities that utilize the internet as a communication medium. Trade, for example, increasingly relies on electronic commerce (e-commerce) as a transaction medium. The aim of this research is law enforcement for companies that carry out electronic transactions via e-commerce in Indonesia and legal protection for users of electronic transactions via e-commerce in Indonesia.From the research results it can be obtained that if business actors do not carry out their obligations, business actors can be punished based on Article 62 UUPK, which reads: